2002
DOI: 10.1007/s00127-002-0533-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of personality disorders, psychotic disorders and affective disorders amongst the patients seen by a community mental health team in London

Abstract: The prevalence of personality disorder is high amongst patients seen by community mental health teams. Possible explanations for this are presented and implications for community care are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 15 publications
5
59
1
Order By: Relevance
“…[14][15][16][17][18][19][20][21] This would be consistent with daily practice noticed in different countries, where care is offered from busy nonspecialised mental health centres. 3,22 From an English study it was concluded that the case-loads of community psychiatric nurses and occupational therapists in community mental health teams contained far more patients with REVIEW ARTICLE Koekkoek et al Community care for severe personality disorder 23 In a comparable study, it was social workers and again occupational therapists who treated most people with personality disorder. 24 A possible explanation is that patients with severe personality disorders are treated by the professionals with the lowest threshold for inclusion in their case-load (i.e.…”
Section: Professionals Providing Community Mental Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21] This would be consistent with daily practice noticed in different countries, where care is offered from busy nonspecialised mental health centres. 3,22 From an English study it was concluded that the case-loads of community psychiatric nurses and occupational therapists in community mental health teams contained far more patients with REVIEW ARTICLE Koekkoek et al Community care for severe personality disorder 23 In a comparable study, it was social workers and again occupational therapists who treated most people with personality disorder. 24 A possible explanation is that patients with severe personality disorders are treated by the professionals with the lowest threshold for inclusion in their case-load (i.e.…”
Section: Professionals Providing Community Mental Healthcarementioning
confidence: 99%
“…Support for this hypothesis is offered by the large percentage of patients with severe personality disorders among the case-loads of community psychiatric nurses and occupational therapists: twice as many as among psychiatrists and psychologists (31% v. 15%). 23 Although these professions may be the principal providers of CMHC, they are virtually absent from the literature on severe personality disorders (e.g. in a guide on personality disorders and community mental health teams, they did not author a single chapter).…”
Section: Professionals Providing Community Mental Healthcarementioning
confidence: 99%
“…in community-based clinical settings qualifying for at least one Axis II diagnosis according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV;American Psychiatric Association, 1994;Keown, Holloway, & Kuipers, 2002). According to the DSM-IV, PDs consist of "an enduring pattern of inner experience and behavior that deviates markedly from the expectations of the individual's culture" and is manifested in at least two of the areas of cognition, affect, interpersonal functioning, and/or impulse control.…”
mentioning
confidence: 99%
“…In several UK studies, the diagnostic case mixes of consumers receiving community mental health care have been described (Greenwood, Chisholm, Burns, & Harvey, 2000;Hunter et al, 2002;Keown, Holloway, & Kuipers, 2002;Newton-Howes et al, 2010). The findings of these studies vary widely, which may be an artifact of the methods employed and the size of the samples.…”
Section: Psychiatric Diagnosismentioning
confidence: 97%